Pengembangan Fitur Lembar Triase Obstetri dalam Rekam Medis Elektronik (RME) Menggunakan OTAS di PONEK RS Tipe B di Kota Cimahi - Darmayanti (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Maternal emergencies require a triage system that is specific, rapid, and accurately documented to reduce maternal and neonatal mortality. However, most hospitals still use general triage systems that are not tailored to obstetric complexity, and electronic medical records (EMRs) often lack dedicated obstetrical triage features. This study aimed to develop a digital obstetrical triage form based on the Obstetrical Triage Acuity Scale (OTAS) integrated into the EMR system of the PONEK unit at B-Type Hospital in Cimahi City. This research employed a Research and Development (R&D) approach using the PPE (Planning, Production, Evaluation) model. The planning stage involved observation and focus group discussions. A prototype triage feature was developed for three categories: early pregnancy, late pregnancy, and postpartum. The evaluation phase included content validity assessment, system feasibility testing, and user satisfaction evaluation. The prototype enabled input of clinical data and automatic OTAS scoring, fully integrated into the hospital’s EMR. Content validity index (CVI) scores reached 1.00, indicating high validity. System feasibility was rated at 87.5% (very feasible), and user satisfaction averaged 4.4 out of 5. The OTAS-based obstetrical triage feature is valid, feasible, and well-received. It enhances clinical decision-making, documentation accuracy, and triage efficiency in maternal emergency care. ABSTRAK. Penelitian ini bertujuan untuk mengembangkan fitur lembar triase obstetri dalam Rekam Medis Elektronik (RME) menggunakan pendekatan Obstetrical Triage Acuity Scale (OTAS) di ruang PONEK RS Tipe B di Kota Cimahi. Desain penelitian menggunakan metode Research and Development (R&D) model PPE (Planning, Production, Evaluation). Tahapan perancangan dilakukan melalui FGD dengan tenaga medis dan IT rumah sakit untuk menggali kebutuhan sistem triase obstetri. Tahap produksi menghasilkan prototype fitur triase yang terdiri dari kategori kehamilan (awal, lanjut, dan pascapersalinan) dengan integrasi skoring otomatis OTAS. Tahap evaluasi dilakukan melalui uji validitas isi, kelayakan sistem, dan kepuasan pengguna. Hasil menunjukkan validitas isi tinggi (S-CVI = 1.00), kelayakan sistem sebesar 87.5% (sangat layak), dan kepuasan pengguna rata-rata 4.4 dari 5. Fitur ini mendukung keputusan klinis cepat, dokumentasi akurat, dan efisiensi pelayanan maternal di PONEK. Kata Kunci: OTAS, RME, Triase Obstetri, Kegawatdaruratan Maternal, PONEK, R&D PPE